Mobility Assistance Programmes for Unemployed Workers, Job Search Behaviour and Labour Market Outcomes - Marco Caliendo; Steffen Künn; Robert Mahlstedt (Institute of Labor Economics (IZA), 2017)
The appealing idea of geographically relocating unemployed job seekers from depressed to prosperous regions and hence reducing unemployment leads to industrialised countries offering financial support to unemployed job seekers when searching for and/or accepting jobs in distant regions. In this paper, we investigate the impact of the existence of these mobility assistance programmes (MAPs) on the job search behaviour of unemployed workers and how this affects their labour market outcomes. While job search theory predicts a shift in individuals' search effort from local to distant labour markets, consequences for other dimensions of the search behaviour, e.g. reservation wages or the overall search effort, and job-finding probabilities remain theoretically ambiguous. We use survey data on German unemployed job seekers and apply an instrumental variable approach to empirically identify the causal impact of an increased search radius, due to the availability of MAPs, on job search strategies and subsequent labour market outcomes. The results show that the existence of MAPs shifts individuals' search effort from local to distant regions without affecting the total number of job applications. The increase in search radius causes a higher geographical mobility and hence higher employment probabilities and wages.
Keywords: J61; J68; D04; C21; 330; job search; active labour market policy; labour market mobility; instrumental variable approach